2004
DOI: 10.3168/jds.s0022-0302(04)73343-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Micronized and Extruded Flaxseed on Ruminal Fermentation and Nutrient Utilization by Dairy Cows

Abstract: Four lactating Holstein cows with ruminal and duo-denal cannulas were used in a 4 x 4 latin square design to determine the effects of feeding heat-treated flaxseed on ruminal fermentation and site and extent of nutrient utilization. Four diets were formulated: a control diet with no flaxseed, a raw flaxseed diet (RF), a micronized flaxseed diet (MF), and an extruded flaxseed diet (EF). Flaxseed diets contained 12.6% flaxseed (dry matter [DM] basis). Ruminal pH, NH3 N, and total concentration of volatile fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

32
90
7
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 44 publications
32
90
7
3
Order By: Relevance
“…According to Martin et al (2008), feeding flaxseed has no negative effect on DM intake and milk yield due to a slow release of fatty acids in the rumen fluid as compared to when flaxseed is fed extruded or as oil. In the present experiment, cows fed the highest level of flaxseed tended to have lower digestibility of DM and N. Decreases (Martin et al, 2008), increases (Gonthier et al, 2004) or no effect (Doreau et al, 2009a) of flaxseed supplementation on digestibility of nutrients by dairy cows have been reported. Martin et al (2008) concluded that the amount of added lipids and their form of presentation (oil v. seed) are major determining factors for the negative effect of flaxseed fatty acids on digestibility.…”
Section: Discussionmentioning
confidence: 70%
“…According to Martin et al (2008), feeding flaxseed has no negative effect on DM intake and milk yield due to a slow release of fatty acids in the rumen fluid as compared to when flaxseed is fed extruded or as oil. In the present experiment, cows fed the highest level of flaxseed tended to have lower digestibility of DM and N. Decreases (Martin et al, 2008), increases (Gonthier et al, 2004) or no effect (Doreau et al, 2009a) of flaxseed supplementation on digestibility of nutrients by dairy cows have been reported. Martin et al (2008) concluded that the amount of added lipids and their form of presentation (oil v. seed) are major determining factors for the negative effect of flaxseed fatty acids on digestibility.…”
Section: Discussionmentioning
confidence: 70%
“…The application of heat treatment to oilseeds such as flaxseed can protect dietary polyunsaturated FA from ruminal BH by denaturing the protein matrix surrounding the fat droplets, thus reducing the access of ruminal bacteria to dietary fat (Kennelly 1996). In a previous study we found that feeding micronized relative to extruded flaxseed to dairy cows decreased (P < 0.05) ruminal and increased (P < 0.05) post-ruminal digestibility of dry matter (DM), fiber and total fatty acids (Gonthier et al 2004). However, the effects of heat treatment on ruminal BH and digestibility of FA from flaxseed have not been determined.…”
mentioning
confidence: 99%
“…The differences decreased after the morning meal and reversed 9 hours later, and the ammonia concentration decreased by 75% at the same time. Gonthier et al (2004) observed small decrease in ammonia production during ruminal fermentation after the addition of flax seeds. On the other hand, a slightly higher concentration of NH 3 in cow rumen was found by Beauchemin et al (2009) after the addition of flax seeds.…”
Section: Discussionmentioning
confidence: 92%
“…Available literature is scant in information about effect of flax seeds on fermentation processes in the caecum of the rabbit. The effect of flax seeds on the profile of microbiological fermentation in the cow rumen was studied by Gonthier et al (2004). The researchers observed decrease in the molar proportion of acetic acid and an increase of propionic acid in flaxseed-fed animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation